The impact of an online adult headache guideline on headache referrals to the neurology clinic. Issue 8 (22nd August 2021) - Huang, Leon; Bourke, David; Ranta, Annemarei
Abstract : Background: Headache is a common problem in primary care and one of the main reasons general practitioners (GP) consult the neurology service. We developed an online adult headache guideline (Supporting Information Appendix S1) for the greater Wellington Region as a resource for GP to guide identification of concerning headaches, initiation of prophylactic medications for migraine and management of analgesic overuse headache. Aims: To examine the effectiveness of this adult headache guideline in reducing demand on the neurology outpatient service for headache patients that could readily be managed in primary care. Methods: We reviewed electronic referrals to Wellington Hospital's neurology department before and after the implementation of the online headache guideline. The primary outcome was the proportion of referrals for headache. Secondary outcomes included proportion of referrals requiring clinic review, rate of pre‐referral trial of headache prophylactic medication and medication overuse headache diagnosed at neurological consultation. Results: Nine hundred neurology referrals before and 801 referrals after the publication of the online headache guideline were included. There was a statistically significant reduction in proportion of referrals for headache (15.4% vs 11.7%; P = 0.026). There was neither an increased rate of pre‐referral adequate prophylactic medication trial (33.8% vs 27.7%; P = 0.320) nor fewer medication overuse headaches diagnosed during the neurology assessment (21.9% vs 25.0%; P = 0.674). Conclusion: The launch of an online headache guideline was associated with a reduction in demand on neurology service. Further education could improve the utilisation of this guideline, to avoid delays in prophylactic treatment and reduce the harm of medication overuse.